A quality-facilitated socialization model of social commerce decisions. (June 2018) - Aladwani, Adel M.
Highlights: Proposes & tests a quality-facilitated socialization model of social commerce decisions. It links initial attention, interaction experience, intuitive evaluation, & buying intentions. Quality of social commerce & social support play differential roles in social commerce events. Theoretical and practical implications of the findings are discussed. Abstract: Many businesses are faced with the challenge of understanding how to facilitate an individual consumer's purchasing decision in the new era of social media. Without effectively addressing this problem, businesses will not be able to seize valuable opportunities to enlarge their customers' base or optimize their social commerce decisions. This study argues that one way to deal with this important issue is through viewing social commerce as a series of engagement events facilitated by quality-augmented socialization process. More specifically, it proposes and empirically examines a new model that connects social commerce quality (perceptive and unperceptive) and social support quality to four interaction events of social commerce, namely initial attention, interaction experience, intuitive evaluation, and intention to buy. The findings of a PLS-SEM modeling of responses collected from a sample of active social media users reveal at least three worth noting findings. First, the present study confirmed that the social commerce process followed a causal path linking an individual consumer's initial attention to interaction experience to intuitive evaluation to intention to buy a product/service. Second, Social support quality was found to significantly influence only a consumer's initial attention, intuitive evaluation, and intention to buy. Third, social commerce quality (both unperceptive and perceptive) was found to significantly influence only a consumer's interaction experience and intention to buy. The theoretical and practical implications of the findings are discussed.